An evaluation of existent methods for estimation of embankment dam breach parameters - Sammen S.S.; Mohamed T.A.; Ghazali A.H.; Sidek L.M.; El-Shafie A. (Springer Netherlands, 2023)
artificial neural network; dam failure; embankment dam; peak discharge; uncertainty analysis